Efficacy and safety of porcine ALG compared to rabbit ATG as first‐line treatment for children with acquired aplastic anemia. (5th March 2020) - Zhu, Yangmin; Yang, Yang; Yang, Wenrui; Song, Lin; Li, Yuan; Fan, Huihui; Li, Yang; Li, Jianping; Ye, Lei; Zhao, Xin; Zhou, Kang; Peng, Guangxin; et al.
Abstract: Objective: To assess the outcomes of children with acquired aplastic anemia (AA) treated in China with first‐line porcine anti‐lymphocyte immunoglobulin (p‐ALG)/rabbit anti‐thymocyte immunoglobulin (r‐ATG) combined with cyclosporine A (CSA). Methods: We performed a single‐center, non‐randomized, retrospective cohort study to assess the outcomes of 189 children with AA treated in China with first‐line p‐ALG/r‐ATG combined with CSA between 2014 and 2018. Results: No significant differences were observed in the overall response rates at 3, 6, 12, or 24 months (3 months: 61.9% vs 67.4%, P  = .5; 6 months: 70.9% vs 73.9%, P  = .69; 12 months: 77.3% vs 73.3%, P  = .58; 24 months: 81.6% vs 78.6%, P  = .59) after either p‐ALG‐ or r‐ATG‐based immunosuppressive therapy. No significant differences were observed in overall survival or failure‐free survival between the p‐ALG group and the r‐ATG group. Conclusion: Our results reveal that the therapeutic efficacy and safety of p‐ALG combined with CSA did not differ significantly from those of r‐ATG combined with CSA as first‐line therapy for pediatric patients with AA. Moreover, p‐ALG has the advantage of significantly lower cost compared with r‐ATG.